Numerical Investigation of Finite Element Torsional Rigidity Revolution in Formula Car - M. K. A. A. Razab, Zairi Ismael Rizman, M. Fadzli Hamid, S. Sa’ad, M. Mazlan, A.S. Sharizal, Ayub Ahmed Janvekar (International Journal of Advanced Science and Technology, 2019)
EIMA Race formula student has become more popular inter institutions that open to the public, private, college, polytechnics and technical higher institution that served education through motorsport. One of the failure manner whenever do a material selection is torsional rigidity endurance. A torsional rigidity has grown to be more specific complex index study, having highly degrees of effect in influences on system operating; therefore, this paper mainly emphasizes the study on finite element calculation based on torsional rigidity. However, in torsional rigidity test can be conduct on most material to determine the torsional and mechanical properties behavior becomes highly concern due to i.e. crack propagation, rapid deformation, failure of properties. The study was conduct by using physics simulation software ANSYS version 15 and 3D CAD design software Solidworks version 2013. From the numerical study found that the torsional rigidity test has in a range of safety factor that could endurance incoming force acting at various region on mild steel AISI1030 hot rolled steel thus ensure the modulus of elastic in shear by mean of twisting test that comply with ASTM-E-143. Keywords: elasticity, EIMA Race, shear test, torsional rigidity test, twisting test